Edukasi Gizi dan Penguatan Konsumsi Tablet Fe pada Remaja Putri di SMK Pariwisata Kertayasa dan SMK Werdi Sila Kumara Kabupaten Gianyar - I Made Purnadhibrata; I Putu Suiraoka (Jurnal Pengabmas Masyarakat Sehat (JPMS), 2019)
Iron deficiency anemia is a nutritional problem that affects more than 600 million people. Estimates of global anemia prevalence are around 51%. WHO data from 1993 to 2005 shows approximately 24.8% or 1.62 billion of the world's population suffer from anemia and 25.4% of them are school-age children. Whereas in Southeast Asia school-age children suffer from anemia by 13.6%. The impact of anemia on young women is that the body during the growth period is easily infected, resulting in reduced fitness / freshness, decreased learning / achievement spirit. This community service aims to provide education on prevention of nutritional anemia in young women through increased knowledge and behavior of consumption of foods high in iron and consumption of iron tablets. Community service was carried out at Kertayasa Vocational School and Werdi Sila Kumara Vocational School from June to July 2018. The sample of this community service was 100 young women, each of 50 people from the Kertayasa Vocational School and 50 WerdiSila Kumara Vocational High School students.The pretest results in the knowledge of anemia showed an average of 88.80 (+8.64) correctly and after educating the post test results showed an increase to an average of 88.50 (+10.11) which was correct. The increase showed very different results (p 0.05).Most samples (61.00%) used to consume Fe tablets between 2-8 tablets per month. Because program giving iron tablets are integrated in schools, most of the samples (86.9%) stated they got iron tablets at school. In an effort to increase the coverage of iron tablet consumption in adolescent girls, it is recommended that regular administration of Fe tablets through schools.Keywords: Nutrition Education, Young Women, Iron supplementation consumption.